Feasibility of generating electricity through gasification of sawmill residues in the North of Mexico - Balderrama-Castañeda, Salvador; Luján-Álvarez, Concepción; Lewis, David K.; Ortega-Gutiérrez, Juan A.; de Jong, Bernardus H.J.; Nájera-Ruiz, Tonatiuh (Instituto de Ecología, A.C., 2016)
The feasibility of converting sawmill residues in electricity through gasification was evaluated in two ejido sawmills, Rocheachi and Tatahuichi, in the Guachochi municipality of Chihuahua State. The area has a semi cold climate, with temperature and precipitation annual means of 10,6 oC and 800 mm, respectively; the tree cover is dominated by pine and pine-oak communities with Pinus arizonica and P. duranguensis being the main species used for logging. The residues flow  was estimated and its chemical composition and heating value characterized. The selected technology was the fixed bed downdraft gasifier; the costs and specifications data were provided by a Chinese supplier. The main assumptions were: 1,3 kgDM/kwh, 80% plant factor, electricity output sold for street lighting at 80% of commercial price. The financial viability was evaluated through the configuration of (100, 200, 400 and 800) kw systems and three scenarios: base, optimistic and pessimistic. The effect of additional revenues from carbon credits sold at the voluntary market at 4, 5 and 6 US$/tCO2 was assessed. The internal rate of return (IRR) increased consistently with increasing the systems’ capacity with the 800kw being the most economically attractive. without carbon credits, the 100 kw system showed no positive values at any scenario whereas the 800 kw system was the only one with positive IRR in all the scenarios with a range of 3% to 13%; the additional revenues from carbon credits added 2,3 and 2,9% to the low and high scenarios, respectively. In the context of the study, the systems evaluated would satisfy the additionality criteria required by the carbon market.